2013
DOI: 10.1177/1545968313478489
|View full text |Cite
|
Sign up to set email alerts
|

Prism Adaptation Improves Ego-Centered but Not Allocentric Neglect in Early Rehabilitation Patients

Abstract: PA is helpful in treating severely impaired patients in the postacute phase, but the effect is restricted to ego-centered neglect. Lesions in the postcentral cortex (middle occipito-temporal, middle temporal, and posterior parietal areas) seem to limit the effect of PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 28 publications
(35 reference statements)
4
40
0
1
Order By: Relevance
“…This is in line with a recent study showing that neglect patients with a motor-intentional deficit benefited from a 2-week program of PA, while patients classified as having primarily a visual-attentional deficit did not benefit (Goedert, Chen, Boston, Foundas, & Barrett, 2014). A further finding of interest for the interpretation of PA effects on single-word reading is a study by Gossmann, Kastrup, Kerkhoff, López-Herrero, and Hildebrandt (2013), who found that PA only affected body-centered neglect and cancellation, but not line bisection. This finding suggests that the reference frames that are predominantly implicated in these tasks may have distinct dynamics of plasticity and therefore respond differently to the spatio-motor recalibration triggered by PA.…”
Section: Discussionsupporting
confidence: 86%
“…This is in line with a recent study showing that neglect patients with a motor-intentional deficit benefited from a 2-week program of PA, while patients classified as having primarily a visual-attentional deficit did not benefit (Goedert, Chen, Boston, Foundas, & Barrett, 2014). A further finding of interest for the interpretation of PA effects on single-word reading is a study by Gossmann, Kastrup, Kerkhoff, López-Herrero, and Hildebrandt (2013), who found that PA only affected body-centered neglect and cancellation, but not line bisection. This finding suggests that the reference frames that are predominantly implicated in these tasks may have distinct dynamics of plasticity and therefore respond differently to the spatio-motor recalibration triggered by PA.…”
Section: Discussionsupporting
confidence: 86%
“…One of these did not report statistical analyses (Keane et al ., ). Of the remaining studies, 11 found an improvement after PA (Farnè et al ., ; Frassinetti et al ., ; Gossmann et al ., ; Humphreys et al ., ; Jacquin‐Courtois et al ., ; Keller et al ., ; McIntosh et al ., ; Nijboer et al ., ; Nys, Seurinck, et al ., ; Serino et al ., ; Vallar et al ., ). Effects were less consistent in four studies.…”
Section: Resultsmentioning
confidence: 99%
“…The terminal feedback procedure was used in 12 studies (Eramudugolla, Boyce, Irvine, & Mattingley, 2010;Fortis et al, 2010;Frassinetti, Angeli, Meneghello, Avanzi, & L adavas, 2002;Mancuso et al, 2012;McIntosh, Rossetti, & Milner, 2002;Priftis et al, 2013;Rusconi & Carelli, 2012;Saevarsson, Kristj ansson, Hildebrandt, & Halsband, 2009;Saevarsson et al, 2010;Serino et al, 2007Serino et al, , 2009Vangkilde & Habekost, 2010). Eleven of these found (some) significant effects of PA. Twelve studies used the concurrent feedback procedure (Farn e, Rossetti, Toniolo, & L adavas, 2002;Gossmann, Kastrup, Kerkhoff, L opez-Herrero, & Hildebrandt, 2013;Jacquin-Courtois, Rode, Pisella, Boisson, & Rossetti, 2008;Keane, Turner, Sherrington, & Beard, 2006;Luaut e et al, 2012;Morris et al, 2004;Nijboer et al, 2011;Nys, Seurinck, & Dijkerman, 2008;Nys, de Haan, et al, 2008;Rossetti et al, 1998;Rousseaux, Bernati, Saj, & Kozlowski, 2006;Sarri et al, 2008), of which nine found (some) significant effects of PA. In several studies the obstruction procedure was not clearly described (Humphreys, Watelet, & Riddoch, 2006;Keller et al, 2009;Saj et al, 2013;Shiraishi et al, 2010;Smit et al, 2013;Vallar, Zilli, Gandola, & Bottini, 2006).…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…For example, reductions in neglect symptoms following rightward prism adaptation have been observed for tasks involving line bisection (Rossetti, Rode, Pisella, Farné, Li, Boisson, & Perenin, 1998; Pisella, Rode, Farne, Boisson, & Rossetti, 2002), shape cancellation (Rossetti et al, 1998; Serino, Bonifazi, Pierfederici, & Ladavas, 2007), body orientation judgments (Gossmann, Kastrup, Kerkhoff, LÓpez-Herrero, & Hildebrandt, 2013), visual search (Saevarsson, Kristjansson, Hildebrandt, & Halsband, 2009), haptic exploration (McIntosh, Rossetti, & Milner, 2002), straight-ahead pointing (Pisella et al, 2002), and attentional disengagement from ipsilesional hemispace (Schindler, McIntosh, Cassidy, Birchall, Benson, Ietswaart, & Milner, 2009). In addition, Bultitude, Rafal, and List (2009) demonstrated that adaptation to rightward-shifting prisms ameliorates the local processing bias of neglect patients.…”
Section: Introductionmentioning
confidence: 99%